Gestão de resíduos em uma panificadora utilizando as técnicas de Produção mais Limpa (P+L) e de educação ambiental - Alves, Mariana Orlandi (Universidade Federal de São Carlos, 2021)
This work aims to analyze the generation and management of solid waste, also improve the environmental management through environmental education focused on clean production, from a bakery located in Juquehy, São Sebastião, in the state of São Paulo. Through weighing experiments and environmental education “classes”, bakery employees are expected to have greater knowledge about urban solid waste management (MSW) and, therefore, to become aware of this very important subject for society today.
Waste management in a bakery using the Cleaner Production and environmental education techniques
Keywords: Gestão de resíduos sólidos; Produção mais limpa; Panificação; Educação ambiental; Process mitigation.; Environmental education; Cleaner production; Waste management; ENGENHARIAS